Genetic suppression of the circadian Clock mutation by the melatonin biosynthesis pathway - Shimomura, Kazuhiro (National Academy of Sciences, 2010)
Most laboratory mouse strains including C57BL/6J do not produce detectable levels of pineal melatonin owing to deficits in enzymatic activity of arylalkylamine N-acetyltransferase (AANAT) and N-acetylserotonin O-methyl transferase (ASMT), two enzymes necessary for melatonin biosynthesis. Here we report that alleles segregating at these two loci in C3H/HeJ mice, an inbred strain producing melatonin, suppress the circadian period-lengthening effect of the Clock mutation. Through a functional mapping approach, we localize mouse Asmt to chromosome X and show that it, and the Aanat locus on chromosome 11, are significantly associated with pineal melatonin levels. Treatment of suprachiasmatic nucleus (SCN) explant cultures from Period2(Luciferase) (Per2(Luc)) Clock/+ reporter mice with melatonin, or the melatonin agonist, ramelteon, phenocopies the genetic suppression of the Clock mutant phenotype observed in living animals. These results demonstrate that melatonin suppresses the Clock/+ mutant phenotype and interacts with Clock to affect the mammalian circadian system.